Intervensi Terapi Musik Terhadap Penurunan Tingkat Cemas Pada Pasien Penyakit Kardiovaskular : Systematic Review - Haris Fadjar Setiawan; Elly Nurachmah; Anggri Noorana Zahra; Agung Waluyo (Jurnal Ners, 2025)
Cardiovascular disease is often characterised by symptoms such as chest pain, palpitations, dyspnoea, excessive sweating, trembling, dizziness, and somatic symptoms such as pain and fatigue. In addition to physical problems, cardiovascular patients also often face psychological disorders, especially anxiety. High levels of anxiety in these patients can hinder the treatment process and worsen their condition. One effective nonpharmacological therapy to reduce anxiety in cardiovascular patients is music therapy, which can help calm and relax patients. Aim: to describe whether music therapy intervention is effective in reducing anxiety levels in cardiovascular patients. Methods: the writing of this article uses a systematic review conducted through a search strategy on 4 databases namely Scopus, scince direct, Pubmed, and Clinical key with a total of 3,824 articles obtained. The articles were then filtered based on inclusion and exclusion criteria to leave 5 articles. A total of 5 articles that met the criteria were then subjected to critical appraisal using the JBI Critical Appraisal Checklist guidelines. Results: In general, this systematic review shows that music therapy intervention is effective in reducing the anxiety level of cardiovascular patients.